Stochastic resonance in symmetric double well: higher harmonics - Zhiglo, A.V. (Вопросы атомной науки и техники, 2001)
The work deals with the phenomenon of Stochastic Resonance in its genuine model, proposed by B. McNamara and K. Wiesenfeld for explanation of long-term climatic changes on Earth. It is shown that in two state model the higher harmonics behave in a non-monotonous way with increase of the noise level, possessing one or more maxima. Explicit formulae for third and fifth harmonic amplitudes and corresponding SNR are obtained. Studied by other authors peculiarities, like dips and sharp peaks in output signal do not occur in two state model, thus they only exist in systems with continuous configuration space.